Investigating Fraud and Corrupt Practices in Indonesia - Siti Kustinah (Journal of Governance, 2022)
Abstract: Many cases of fraud that occurred in public and private sectors resulted in losses. There are state and state financial losses in the public sector, while in the private sector, there are also losses arising from a breach of contract in an engagement. Fraud is an act that is against the law and is done intentionally. The impact of fraud and corruption will increase the amount of stolen state money, and the provision of development or investment will be significantly hampered, especially in the case of foreign investment. When issues of fraud in financial statements are discovered, efforts must be made to prevent or minimize the occurrence of such claims. One way to achieve this is to study forensic accounting. By understanding forensic accounting, apart from being reliable in preparing financial reports, it is also claimed to read what is contained in one of these documents. Law enforcement can benefit from the expertise of accountants, particularly those working in forensic accounting, to disclose and provide evidence to support court decisions relating to corruption, as discussed in this paper. In addition, this paper will discuss forensic accounting and forensic auditing and efforts that can be made to prevent corruption and fraud.Keywords: Fraud, Corrupt Practices, Forensic Accounting, Audit.